2022
DOI: 10.1101/2022.03.29.22273086
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age and product dependent vaccine effectiveness against SARS-CoV-2 infection and hospitalisation among adults in Norway: a national cohort study, July – November 2021

Abstract: Background: COVID-19 vaccines have been crucial in the pandemic response and understanding changes in vaccines effectiveness is essential to guide vaccine policies. Though the Delta variant is no longer dominant, understanding vaccines effectiveness properties will provide essential knowledge to comprehend the development of the pandemic and estimate potential changes over time. Methods: In this population-based cohort study, we estimated vaccine effectiveness against SARS-CoV-2 infections, hospitalisati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
3
1
0
Order By: Relevance
“…Our results are also consistent with other reports of waning protection after three mRNA doses 232425. As with others, we noted less waning against more severe outcomes,326 lower vaccine effectiveness among individuals who were immunocompromised,1727 and higher vaccine effectiveness among recipients of mRNA-1273 compared with recipients of BNT162b2 102324. We also observed improvement in vaccine effectiveness after a fourth dose 28…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are also consistent with other reports of waning protection after three mRNA doses 232425. As with others, we noted less waning against more severe outcomes,326 lower vaccine effectiveness among individuals who were immunocompromised,1727 and higher vaccine effectiveness among recipients of mRNA-1273 compared with recipients of BNT162b2 102324. We also observed improvement in vaccine effectiveness after a fourth dose 28…”
Section: Discussionsupporting
confidence: 92%
“…Our vaccine effectiveness estimates for mRNA vaccines are broadly consistent with those in other reports: vaccine effectiveness was lower against the omicron variant than earlier variants,102122 vaccine effectiveness waned after a second dose,3456789 and a third dose restored high levels of protection against severe covid-19 during the omicron and delta periods 10111213. Our results are also consistent with other reports of waning protection after three mRNA doses 232425. As with others, we noted less waning against more severe outcomes,326 lower vaccine effectiveness among individuals who were immunocompromised,1727 and higher vaccine effectiveness among recipients of mRNA-1273 compared with recipients of BNT162b2 102324.…”
Section: Discussionsupporting
confidence: 91%
“…RR estimates obtained using a retrospective 4-week sliding window are reported in Figure 1, and estimates obtained for larger periods are reported in Table S2. As shown in both Figure 1 and Table S2, our results also confirm notable variations in the apparent protective effect of the vaccine between different age categories, with the RR estimates increasing globally with age [21][22][23]. In particular, sliding window estimates (Figure 1) indicate that at the beginning of the study period, RR estimates started rather high for people above 75 years old (75-85: RR = 0.34, 95% CI = [0.27-0.42]; 85+: RR = 0.65, 95% CI = [0.48-0.87]), which is compatible with an effect of waning immunity, the vaccination campaign for these two age categories having started early 2021.…”
Section: Resultssupporting
confidence: 79%
“…To our knowledge, few studies have evaluated the effectiveness of heterologous 2-dose schedules. Two other studies also found that heterologous and homologous mRNA vaccine schedules had equivalent VE estimates [ 11 , 24 ]. A Danish study found that VE against any infection for heterologous ChAdOx1 and mRNA vaccine schedules was 88% (95% CI, 83%–92%) ≥14 days after the second dose, which is comparable to our VE estimates against any infection at 7–59 days (VE ChAdOx1/BNT162b2 = 90% [95% CI, 88%–92%]; VE ChAdOx1/mRNA-1273 = 91% [95% CI, 89%–93%]), but did not assess duration of effectiveness [ 20 ].…”
Section: Discussionmentioning
confidence: 88%